Is the current therapeutic dosage of nadroparin adequate for neonates and infants under 8 months with thromboembolic disease? a population pharmacokinetic study from a national children’s medical center - Chen, Yewei; Lan, Jianger; Zhu, Lin; Dong, Min; Wang, Yi; Li, Zhiping (Frontiers in Pharmacology, 2024)
Objectives: Nadroparin, a low-molecular-weight-heparin is commonly used off-label in neonates and infants the neonatal intensive care unit (NICU) for thromboembolic events prevention. However, the recommended dosing regimen often fails to achieve therapeutic target ranges. This study aimed to develop a population pharmacokinetic (PK) model of nadroparin to determine an appropriate dosing regimen for neonates and young infants less than 83 months.Methods: A retrospective chart review was conducted on critically ill patients treated with nadroparin in NICU at Children's Hospital of Fudan University between July 2021 and DecemberJuly 2023. A population PK model was developed using anti-Xa levels, and its predictive performance was evaluated internally and externally. Monte Carlo simulations were performed to design an initial dosing schedule targeting anti-Xa levels between 0.5 and 1 IU/mL.Results: A total of 4024 neonates and young infants aged less than 8 months with gestational age ranging from 28 to 41 weeks treated with nadroparin were enrolled in the study for analysis. A one-compartment PK model with first order absorption and elimination was adequately fitted to the data. Creatinine clearance was No covariates were identified as a significant factors contributing to inter-individual variability in clearance. The typical population parameter estimates of clearance, distribution volume and absorption rate in this population were 0.211181 L/h, 1.557 L and 0.495522 h -1 , respectively. Our findings suggest that current therapeutic doses of nadroparin (150-200 IU/kg q12h) may result in subtherapeutic exposure, thus higher doses might be required.The present study offers the first estimation of PK parameters for nadroparin in preterm or term neonates and young infants less than 83 months utilizing 3 the model. Our findings have potential implications for recommending initial personalized dosages, particularly among patient populations exhibiting similar characteristics.